Effect of nonsteroidal anti-inflammatory drug Rofecoxib (Vioxx™) on the bone repair - Luiz Alberto Milanezi; Tetuo Okamoto; Victor Prado Curvêllo (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the effect of the nonsteroidal anti-inflammatory drug Rofecoxib (Vioxx™) on the bone repair process in the tibiae of stressed rats. Methods: In this study, use was made of 48 young male (Albinus Wistar) rats weighing between 150 and 200 grams, divided into three groups of 16 animals each. The following procedures were performed: Group I was used as the control group, and in it, only the bone defect was performed; in Group II the animals received stressor stimulus in the three pre-operative days and three post- operative days after the defect was performed, up to the time of sacrifice; in Group III the animals received the administration of nonsteroidal anti-inflammatory medication (pre-operatively), stressor stimulus one hour after drug administration, in the pre-operative period, bone defect and stress in the post-operative period, up to the time of sacrifice. In groups of four, the animals were sacrificed at 7, 14, 30 and 60 post-operative days, by means of cervical column dislocation. After being sacrificed, the right and left tibiae were removed, fixed in formalin, decalcified in ethylenodiaminatetracetic acid (Na.2H2.2H2O) and included in paraffin. Cuts of 6 micrometers thickness were stained with hematoxylin and eosin for microscopic analysis. Results: The results obtained were described as a function of the post-operative time of the histomorphologic occurrences observed in the different experimental groups. Conclusion: The results allowed one to conclude that: 1) repair of the bone defect caused in the rats of Group II were shown to be more delayed than those in Group I; 2) repair of the bone defect caused in the rats of Group III were shown to be less delayed than those in Group II; 3) the prescription of the anti-inflammatory drug Rofecoxib can be indicated in the case of experiments with stressed animals, because it diminished the effect of stress on bone repair, in the case of defects caused in the tibia of rats.